أزمة قيم المواطنة وتداعياتها على الاستقرار الأمني للمجتمعات العربية في زمن الأزمات - النوي ،بالطاهر; عاتكة، غرغوط (جامعة المونستير - سوسة- تونس, 2025)
تتناول هذه المداخلة أزمة قيم المواطنة في المجتمعات العربية وتداعياتها المباشرة على الاستقرار الأمني في زمن الأزمات المركبة. ينطلق التحليل من فرضية أن المواطنة ليست مجرد رابطة قانونية، بل منظومة قيمية ترسخ المشاركة والمسؤولية والعدالة والمساواة، وأن ضعف هذه القيم يقوض العقد الاجتماعي ويعمق أزمة الثقة بين المواطن والدولة. تبين الدراسة أن تآكل قيم المواطنة يؤدي إلى زعزعة الاستقرار السياسي، انتشار التطرف والإرهاب، هشاشة الدولة وتفككها، وتداعيات إقليمية ودولية تشمل التهجير القسري والجريمة المنظمة. وتقترح الورقة مسارات عملية لإعادة تأسيس قيم المواطنة، من خلال إصلاح العقد الاجتماعي، تبني سياسات إدماجية عادلة، إدماج التربية على المواطنة في المناهج، تمكين الشباب والنساء، واعتماد حوكمة أمنية قائمة على الحقوق. وتخلص المداخلة إلى أن تعزيز المواطنة الفاعلة ليس مجرد استحقاق ديمقراطي أو اجتماعي، بل يمثل استثمارا أمنيا ضروريا لضمان استقرار الدول والمجتمعات العربية في مواجهة الأزمات Abstract: This paper addresses the crisis of citizenship values in Arab societies and its direct implications for security and stability in times of complex crises. It argues that citizenship should not be reduced to a legal status but understood as a set of values—participation, responsibility, justice, and equality—that reinforce the social contract. The erosion of these values undermines trust between citizens and the state, weakening social cohesion. The study shows that the decline of citizenship values leads to political instability, the spread of extremism and terrorism, state fragility and disintegration, as well as regional and international consequences such as forced displacement and organized crime. It further proposes practical pathways for restoring citizenship values through social contract reform, inclusive policies, civic education, empowerment of youth and women, and rights-based security governance. The paper concludes that fostering active citizenship is not only a democratic or social imperative but also a crucial security investment for the stability of Arab states and societies in the face of crises.
Intervention
Keywords: المواطنة; الأمن المجتمعي; العقد الاجتماعي; التطرف; الاستقرار السياسي; ، العالم العربي; الأزمات المركبة; Citizenship; Community Security; Social Contract; Extremism; Political Stability; Arab World; Complex Crises